The Role of Knowledge Management in Higher Education Institutions (Colleges and Universities) - Saeed, Sarkar Ahmed; Tofiq, Ako Mohammed; Qadir, Aram Mohammed-Amin; Faraj, Shahen Mohammed; Aziz, Khanda Gharib (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The objective of this study is to understand the role of knowledge management in higher education institutions. This study aims to know to review the literature on knowledge management in general and its application to higher education institutions in particular. This study shows the importance of the KM in the academic sector or the role of the KM in advancing higher education. Indeed, the academic environment is a treasure trove of knowledge, but it is not well organized and therefore also useless and leads to repetition of the activity. However, KM has been accepted in a large number of sectors, organizations, institutes, universities, colleges, and the higher education sector in general, and the full potential of KM has been delivered. Previous research also sought to shed light on the importance of linking study with higher education. The contribution of this study is a practical and actionable step-by-step plan as well as a theoretical framework for the importance of the role of successful knowledge management in higher education institutions.